Analisis Kapasitas Maksimum Sungai Juana dalam Mengatasi Banjir saat Debit Air Bendung Wilalung Meningkat (Indonesian Journal of Civil Engineering Study, 2026)
Juana River has a watershed area of ​​1,374.61 km2 stretching 67.26 km across Kudus Regency and Pati Regency, Juana River plays a vital role in Pati Regency and its surroundings. However, this river often faces flooding problems, especially when there is an increase in water discharge from the Wilalung Dam. This condition is exacerbated by sedimentation factors, narrowing, and changes in land use along the river flow. This study aims to analyze the maximum capacity of the Juana River in overcoming flooding when the Wilalung Dam water discharge increases. The research methods used include collecting secondary data in the form of rainfall data, topographic data and morphology of the Juana River, the data was obtained through BBWS Pemali Juana and other related agencies. These data are then processed and analyzed using HEC-RAS 6.1 to model river water flow and predict maximum capacity. The results of the hydrological analysis using the Nakayasu HSS method, the planned flood discharge with a 50-year return period of Q = 545 m3/s The river capacity was simulated by dividing the flow discharge to the Juana River by 50 % to 290 m3/s, Hydraulic analysis using HEC-RAS 6.1 software, the simulation results showed that there was still overflow on the existing and planned cross-sections, but the overflow on the planned cross-section was relatively reduced by 28.19 %. To overcome the overflow in the upstream section, a change in the cross-section design was planned with a base width of 30 m, a top width of 38 and a depth of 7 m. Land use arrangements to build flood control dams or carry out river diversion planning schemes used to slow down the flood arrival time and reduce the magnitude of the flood discharge.
Keywords: Flood Control Dams; Hydrological Analysis; Overflow; River; Upstream